Dashboard for Social Media Marketing Analysis Between B2B Company (Pepsi vs Coca-Cola) - Puventheran, Sonia; Abu Bakar, Juhaida; Katuk, Norliza; Sharipudin, Mohamad Noor Salehhuddin (Multidisciplinary Applied Research and Innovation, 2021)
Social media analytics is a method for social network data such as Facebook, Instagram, LinkedIn, and Twitter to be gathered and evaluated. Marketers typically use it to monitor online discussions about goods and businesses. There is a lack of knowledge about social media analysis in society and the amount of unstructured data is increasing, which takes more time to analyze. The goal of this study is to look at the features of these two B2B companies’ tweets. The Dashboard for Social Media Marketing Analysis between B2B Companies (Pepsi vs Coca-Cola) was created to analyze the behavior of Twitter users based on the way they tweet about these two B2B companies. The dashboard focused on the behavior of Twitter users based on the time and dates that they tweet by looking at the number of favorites and retweets. Then, using sentiment analysis on user tweets, the dashboard examines the Twitter users' behavior. Finally, we created a prototype of a dashboard for B2B companies' social media marketing analysis. Looking at the sentiment analysis page assists the B2B company in identifying issues that occur on social media, which also assists the B2B company in improving their business performance. Knowledge Discovery in Databases (KDD) and qualitative metric data in conjunction with KNIME software are used for the methodology. The dashboard can provide benefits for greater understanding of how social media analysis is important in the new business era.